Impact of Nigeria Police Force Microfinance Bank on the Sustainable Growth of Small and Medium Enterprise in Oshogbo Metropolis - Kolade Akinpelu Ayobami; OLATUNJI Olarenwaju Patrick; OLALEYE Olumide Olalekan; IYUN Moses Oluremi; OCHEI Ngozi Fidelia (ILORIN JOURNAL OF ADMINISTRATION AND DEVELOPMENT UNIVERSITY OF ILORIN, KWARA STATE, 2023)
It is impossible to overstate the importance of small and medium-sized businesses in creating jobs, reducing poverty, fostering economic growth, and increasing productivity. This study set out to investigate how the Nigeria Police Force Microfinance Bank affected the long-term development of SMEs in the Osogbo Metropolis. Data for this study was gathered from SMEs owners in Osogbo Metropolis who had accounts with NPF Microfinance Bank using a questionnaire. The Taro Yamane formula was utilized to determine the sample size. 322 of the 387 distributed questionnaires were deemed viable for analysis using regression analysis and SPSS software. There were two sections on the questionnaire. The demographic characteristics are in Section 1, and the questions on loan approval limit, loan criteria, turnover range, and access to finance for SMEs growth are in Section 2. MFB provides financial services, collateral for loan access, credit facilities to help low-income individuals, environmental development contributions, and loan services to support SMEs' survival. The results of the study showed that, with a value of.914 P <.05 and a t-value of 33.818, microfinance banks do not significantly affect the growth of SMEs. With a beta value of.732, a P <.05, and a t-value of 16.119, the six Cs of lending have an impact on MFB's capacity to lend to SMEs. The study suggests that NPF Microfinance Bank, particularly for the owners of SMEs, should ease the requirements for borrowing and lengthen the loan period for their clients. They should spread out the repayment over a lengthy period, and the Central Bank of Nigeria should examine and regulate the interest rate that the bank charges to protect small and medium-sized business owners from excessively high-interest rates. The NPF microfinance bank should increase its capacity by establishing a branch in each town in the selected area, especially in the rural areas. This will make the SME owners cultivate the habit of banking, which will enable them to access the facility of loans that will increase their productivity and growth, which will sustain their businesses and move them to the next level of operation.
Keywords: Bank; Growth; Microfinance; Small and Medium-Sized Enterprises